The Communication Style of Americans In ‘The Stars Shine Down’ by Sidney Sheldon - Fitri Setyani; Sunardi; Bibit Suhatmady (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2020)
This study analyzes the communication style of Americans in novel tilted “The Stars Shine Down” by Sidney Sheldon. It is important to be analyzed because if people control their communication style, they can control the outcome of most interactions and avoid the conflict or misunderstanding that caused by communication problem. The analysis of characters’ communication was based on McCallister’s theory (1994) to determine the patterns of communication style. The patterns were divided into three communication styles. It was Dominant Style which was included Noble, Reflective, and Socratic. Then, Blended Style consisted of Magistrate and Candidate. Also, Dual Style was known as Senator. Furthermore, this study was designed in the form of a content analysis of qualitative design. The source of data was the dialog of the main and supporting characters in the novel “The Stars Shine Down” by Sidney Sheldon which supported by the author’s narrative of novel. Moreover, this study used two validators to increase the credibility of the findings and interpretation the communication style. The results for the research question showed that Magistrate and Senator were mostly used by Lara for communication. Then, Noble was utilized dominantly by Paul in his communication which was influenced by the social status. Meanwhile, other style such as Socratic and Candidate were found in most of Howard‟s interaction. Even if all of the communication styles were reflected to the characters, the difference of frequency figures in using communication style was not too excessive for each style. Also, with using of communication style, both of main and supporting character can control the outcome of interaction. It can be related to students’ communication and material of teaching and learning English Thus, it is important for the students and lecturers to understand communication style in their interaction with foreign language speakers, especially Americans to avoid the misunderstanding of communication and control the outcome of interaction